2020
DOI: 10.3389/fimmu.2020.01362
|View full text |Cite
|
Sign up to set email alerts
|

Application of Outer Membrane Protein-Based Vaccines Against Major Bacterial Fish Pathogens in India

Abstract: Aquaculture is one of the fastest-growing food-producing sectors in the world. However, its growth is hampered by various disease problems due to infectious microorganisms, including Gram-negative bacteria in finfish aquaculture. Disease control in aquaculture by use of antibiotics is not recommended as it leads to antibiotic residues in the final product, selection, and spread of antibiotic resistance in the environment. Therefore, focus is on disease prevention by vaccination. All Gram-negative bacteria poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 123 publications
0
28
0
Order By: Relevance
“…Omp has long been recognized as a potential vaccine candidate in most Gram-negative bacteria, owning to its highly conserved region across serotypes and virulence attributes [99]. Besides, scholars reported the antigenic sites of OmpK and OmpW of V. alginolyticus consisting of 34 and 27 antigenic sites, respectively, and deemed suitable for vaccine candidates [57].…”
Section: Development Of a Vaccine Against V Alginolyticusmentioning
confidence: 99%
“…Omp has long been recognized as a potential vaccine candidate in most Gram-negative bacteria, owning to its highly conserved region across serotypes and virulence attributes [99]. Besides, scholars reported the antigenic sites of OmpK and OmpW of V. alginolyticus consisting of 34 and 27 antigenic sites, respectively, and deemed suitable for vaccine candidates [57].…”
Section: Development Of a Vaccine Against V Alginolyticusmentioning
confidence: 99%
“…Proteins were localized in extracellular matrix (3), cytoplasm (7), cytoplasmic membrane (3) and outer membranes (2), besides some of them being predicted with unknown cellular location (5). Of these, surface/outer membrane proteins and vesicles have been deployed for prospective vaccinations against bacterial pathogens [91][92][93][94]. Again, extracellular proteins have been potentiated as drugs for prospects against disease management, albeit, in a different scenario [95,96].…”
Section: Initial Screening Of the Candidate Proteinsmentioning
confidence: 99%
“…Some OMPs can also contribute to the adhesion and colonization of bacteria in the host (Vaca et al 2020) and are important virulence factors of bacteria (Xu et al 2020). OMPs are in the outermost layer of bacteria (the epitope is exposed) and are easily recognized by the host immune defense system to stimulate the immune response (Maiti et al 2020). Previous studies have shown that outer membrane proteins A, C, F, and H have a better antigenicity and immunogenicity, activating the immune functions of animals (De Mot et al 1994;Pore and Chakrabarti 2013;Lee et al 2005;Diao et al 2020), and improved the resistance of animals to bacterial infection, having prospective applications in protein subunit vaccines.…”
Section: Introductionmentioning
confidence: 99%